PELATIHAN MEMUKUL DENGAN BEBAN MENINGKATKAN KECEPATAN PUKULAN LURUS KIRI-KANAN DARI PADA PELATIHAN MENDORONG KATROL DENGAN BEBAN - Imakulata Magi Loda (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2017)
Background: Straight punch or jab punch is one punch in boxing. Jab is a blow provocation done by hand in the front position to distract the opponent. Not infrequently blow jab could be ejected violently. Speed jab is in need to knock out the opponent. Therefore we need the right training. Objective: Training hit by the load and drive pulley with weights aims to increase the speed of the jab and stright punch blow. Method: Experimental research has been done with the design Randomized Pre-Post Test Control Group Design on Student SKO Flobamora Kupang. Total sample of 18 people, divided into two groups and each group of nine people.Group 1 was given training with weights and hit the second group training encourages pulley with weights. Research for six weeks with a frequency of exercise three times a week. speed ismeasured with a stopwatch, before and after treatment, and the differences were statistically tested. Result: T independent test shows the speed among the groups before the training did notdiffer 24.44 plus minus 0.882 /5 seconds. After training the average speed punch 24.44 plus minus 0.882 blow before training 21,00 plus minus 1,118 blows / 5 seconds and average power punches 33.11 plus minus 1.900 blows / 5 seconds. In Group 2 average speed of 33.56 plus minus 1.590 kg. Average speed punch after training were 29.11 plus minus 1,364 blows / 5 seconds. Results of paired t-test showed the average speed of a punch in Group 1 before training 21.33 plus minus 1,118 (p bigger than 0.05) and after training was significantly different (p smaller than 0.05) test shows Training hit with loads more increase the speed of the push pulley with weights. Conclusion: Training concluded hit with a load greatly increase the speed of the left and right straight punches instead of pushing a pulley with weights together to give the effect of increased power and speed and a left straight punch right (p smaller than 0.05). An increase in one group is better than the training push pulley with weights on the speed of the left and right straight punches. Suggestion: It is advisable to use hitting training with weights in the training process in the recruitment of athletes because it gives a better effect.